Penerapan Fuzzy Logic Untuk Menentukan Indeks Massa Tubuh (IMT) Berbasis Internet of Things (IoT) - Ardi Apriansyah; Ahmad Fauzi; Sutan Faisal (Universitas Budi Darma, 2023)
A person's Body Mass Index (BMI) can be determined using the parameters of body weight and height. In manual measurements, to determine BMI, measurements of body weight and height must be carried out and then the BMI results are calculated, so it is felt that it still requires effort and is less effective. Then a tool is made to determine BMI using the Fuzzy Logic method by measuring body weight and height in one step. This Fuzzy Logic method is used to determine the membership status of weight and height. Fuzzy set of weight and height that has been adjusted to the threshold in Indonesia, including weight 35-55 low status, 44-66 normal status, 54-80 heavy status, and height 145-165 low status, 149-176 status normal, 159-190 high status. Software testing results have successfully displayed the results of both sensors, namely, body weight 69.43 Kg with Fuzzi weight status and 161 cm height with normal Fuzzi status. The results of the measurements of the two sensors will also be stored in a database and then displayed on a web containing historical information to find out when the body was last weighed. Then the test results on the LCD Hardware have been able to display a person's weight with a weight of 53 Kg and a height of 171 cm. After testing, these scales have been able to determine the results of a person's body BMI and the two sensors on the scales have been able to determine a person's weight and height.